Study on the alkaline activation of palm oil fuel ash in fly ash based geopolymer concrete containing oil palm shell - Muhammad Aifa , Mohamad Suhaimi (2013)
Malaysia as the world's largest exporter of palm oil has been facing problems- in disposing palm oil fuel ash, a by-product of palm oil mill since many years ago. Through public concerns and research efforts, the agrowaste by-product materials Have potential to be utilized as construction material to replace conventional ordinary Portland cement (OPC). In this study, the effectiveness of agrowaste ash by-product namely palm oil fuel ash (POFA) and oil palm shell (OPS) were developed as an alternative, materials to replace the OPC. POFA fly ash-based concrete is a concrete produced by integrating POFA as a pozzolan in concrete. The quality of POFA was improved by grinding until the median particle sizes were 50 microns. POFA was replaced fly ash by 0%, 10%, and 20%, whereas OPS were replaced sand by 12.5%. The compressive strength of POFA-concretes due to 1, 7, and 28 days of curing ages of different temperature were investigated. The temperatures involved in this experiment were room temperature, 60°C and 80°C. In addition, the porosity of geopolymer concretes fly ash based also was assessed. The results revealed that the compressive strength of geopolymer concrete by the addition of POFA was much lower than that of geopolymer concrete without POFA. The control mixtures for this experiment have the high compressive strength compare to the mixtures added with POFA for all the curing temperature. However, the replacement of POFA by 20% recorded the highest in strength compared to 10% POFA replacement. It is recommended that the optimum replacement levels of POFA are 20% mixture for a good strength in compressive test.